Postoperative Radiation Therapy With or Without Concurrent Chemotherapy for Node-Positive Thoracic Esophageal Squamous Cell Carcinoma - Chen, Junqiang; Pan, Jianji; Liu, Jian; Li, Jiancheng; Zhu, Kunshou; Zheng, Xiongwei; Chen, Mingqiang; Chen, Ming; Liao, Zhongxing (International journal of radiation oncology, biology, physics, 2013)
To retrospectively compare the efficacy of radiation therapy (RT) and chemotherapy plus RT (CRT) for the postoperative treatment of node-positive thoracic esophageal squamous cell carcinoma (TESCC) and to determine the incidence and severity of toxic reactions. We retrospectively reviewed data from 304 patients who had undergone esophagectomy with 3-field lymph node dissection for TESCC and were determined by postoperative pathology to have lymph node metastasis without distant hematogenous metastasis. Of these patients, 164 underwent postoperative chemotherapy (cisplatin 80 mg/m2, average days 1-3, plus paclitaxel 135 mg/m2, day 1; 21-day cycle) plus RT (50 Gy), and 140 underwent postoperative RT alone. The 5-year overall survival rates for the CRT and RT groups were 47.4% and 38.6%, respectively (P=.030). The distant metastasis rate, the mixed (regional lymph node and distant) metastasis rate, and the overall recurrence rate were significantly lower in the CRT group than in the RT group (P<.05). However, mild and severe early toxic reactions, including neutropenia, radiation esophagitis, and gastrointestinal reaction, were significantly more common in the CRT group than in the RT group (P<.05). No significant differences in incidence of late toxic reactions were found between the 2 groups. Our results show that in node-positive TESCC patients, postoperative CRT is significantly more effective than RT alone at increasing the overall survival and decreasing the rates of distant metastasis, mixed metastasis, and overall recurrence. Severe early toxic reactions were more common with CRT than with RT alone, but patients could tolerate CRT.